Microorganism composite bacterium agent and preparation method and application thereof - MOU ZISHEN; LU WENJING; WANG HONGTAO; YANG BOJING (2010)
The present invention discloses a microbe composite bacteria agent and its preparation method and uses. The bacteria agent is composed of primary and secondary ferment bacteria agent. The active ingredient of primary ferment bacteria agent is one or more bacteria strain selected from thermus aquaticus, bacillus sterothermophilus, coccobacillus, sphaerobacter thermophilus sp. and Bacillus acidocaldarius. Each bacteria strain account for 20-100 shares. The active ingredient of secondary ferment bacteria agent one strains selected from Bacillus pasteurii, Bacillus cereus, Aureobacterium liquefaciens, Microbacterium lactium, T salt bacillaceae, Aeromicrobium erythreum, Cellulomonas flavigena, CellulomonasFlavigena or several Lignocellulose degradation bacteria and one strain or several from Trichoderma viride, Pichia pastoris, aspergillus niger lignocellulose degradation fungus combination. Each strain account for 10-50 shares. The present invention has importance to reducing and treatingwaste of high lignocellul